Epitope specificity of antibody-mediated protection induced in mice by the malaria vaccine RTS,S/AS01 - Yevel Flores-Garcia; Berenice Salgado-Jimenez; Minah Park; Shamika Mathis-Torres; Emily Locke; Randall S. MacGill; Re’em Moskovitz; Ian A. Wilson; Fidel Zavala (npj Vaccines)
Abstract Antibodies induced by the malaria vaccine RTS,S/AS01 neutralize infectivity of transgenic sporozoites expressing Plasmodium falciparum CSP (PfCSP). These antibodies recognize the junctional, minor repeats, central repeats, and C-term regions of this antigen. The epitope specificity of antibodies mediating protection in mice was characterized in vivo using transgenic sporozoites expressing restricted antigenic portions of PfCSP. In this model, we found protection is mediated mostly by antibodies specific for the central repeats.